Increased Expression of Integrin Alpha 6 in Nucleus Pulposus Cells in Response to High Oxygen Tension Protects against Intervertebral Disc Degeneration. (18th October 2021) - Xu, Zeng; Zheng, Jiancheng; Zhang, Ying; Wu, Huiqiao; Sun, Bin; Zhang, Ke; Wang, Jianxi; Zang, Fazhi; Zhang, Xingkai; Guo, Lei; Wu, Xiaodong
Abstract : The destruction of the low oxygen microenvironment in nucleus pulposus (NP) cells played a critical role in the pathogenesis of intervertebral disc degeneration (IVDD). The purpose of this study was to determine the potential role of integrin alpha 6 (ITG α 6) in NP cells in response to high oxygen tension (HOT) in IVDD. Immunofluorescence staining and western blot analysis showed that the levels of ITG α 6 expression were increased in the NP tissue from IVDD patients and the IVDD rat model with mild degeneration, which were reduced as the degree of degeneration increases in severity. In NP cells, the treatment of HOT resulted in upregulation of ITG α 6 expression, which could be alleviated by blocking the PI3K/AKT signaling pathway. Further studies found that ITG α 6 could protect NP cells against HOT-induced apoptosis and oxidative stress and protect NP cells from HOT-inhibited ECM protein synthesis. Upregulation of ITG α 6 expression by HOT contributed to maintaining NP tissue homeostasis through the interaction with hypoxia-inducible factor-1 α (HIF-1 α ). Furthermore, silencing of ITG α 6 in vivo could obviously accelerate puncture-induced IVDD. Taken together, these results revealed that the increase of ITG α 6 expression by HOT in NP cells might be a protective factor in IVD degeneration as well as restore NP cell function.